Implementasi Metode Moving Average dalam Analisis Rantai Pasok Daging Sapi di Indonesia - Lintang Dandung Prakoso; Darmansah Darmansah; Tri Widia; Hanin Salma Hanifah (JURIKOM (Jurnal Riset Komputer), 2022)
Beef is meat that comes from common or common cattle and is suitable for food consumption and does not trigger health problems for those who consume it. The need for beef consumption in Indonesia has not been fulfilled because beef production has decreased. This research discusses the analysis of the beef supply chain in Indonesia using the moving average method for forecasting the amount of beef consumption and production in Indonesia in 2022 and using the dextructive analysis method to analyze problems in the supply chain. The data source in the research is based on data available at the National Statistics Agency. And the forecast results show that beef consumption in Indonesia in 2022 will increase by around 0.10% from 2021. However, this is inversely proportional to the amount of production which has decreased by 1.79% from 2021. The results of this study show that the cause of the decline in beef production in Indonesia is in the supply chain for the on-farm sector, including some traditional cattle farmers, human resources, lack of facilities and infrastructure and feed resources.